A Description of Medication Therapy Management Services in Minnesota - Amie Jo Digatono (University of Minnesota Libraries Publishing, 2011)
Objective: To describe Medication Therapy Management (MTM) services in Minnesota, quantifying how many patient encounters occur per week and compiling provider and practice site characteristics. Design: Cross-sectional study. Setting: Minnesota practice sites surveyed in June and July 2010. Participants: MTM providers in Minnesota who are registered users of the Assurance™ documentation system or are members of the Minnesota Pharmacists Association MTM Academy. Intervention: Self-administered online questionnaire completed by study participants. Main Outcome Measures: The number of patient encounters per week, practice site location, practitioner length of time as a MTM service provider, and the motivating factors for providing direct patient care services. Results: There were 56 respondents, reporting a median of 5 MTM patient encounters per week (range 0 to 35) and a median length of service of 4 years (range15). Clinic-based practices were reported by 66% of providers and community pharmacy-based practices by 30%. Eighty-five percent practice in an urban setting, 9% in a large rural town and 6% in a small rural town. Nearly half (46%) of providers are the sole practitioner at their site. The most commonly cited motivation for providing direct patient care services was to improve patient outcomes. Conclusion: MTM service providers in Minnesota were more likely to report practicing in an urban area and in a clinic. Many practices were low-volume or newly established, with half of all respondents reporting 5 or fewer MTM patient encounters per week and a length of service of four years or less. Type: Student Project